Synthesis, Structural and Optical studies of SnO2 nanoparticles by Chemical precipitation method - N Ganeshan S (International Journal of Science and Engineering, 2019)
Tin Oxide (SnO2) nanoparticles have been prepared by chemical precipitation method. The prepared sample was characterized by X-ray diffraction, SEM with EDAX, UV- Vis absorption and Photoluminescence. From the X-ray diffraction patterns showed that the formation of pure SnO2 with their average crystallite size are 17 nm. The crystalline product shows good morphology with meragre agglomeration by SEM images. Elemental compositions of SnO2 nanoparticles were determined by EDX Spectroscopy. UV – Visible spectrum reveals that the transparency of nanoparticles over entire range. The Photoluminescence spectrum for the prepared samples was also recorded.